2016
DOI: 10.1136/bmjopen-2015-009974
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to staying in work after stroke: insight from an online forum

Abstract: ObjectiveTo explore barriers and facilitators to staying in work following stroke.DesignQualitative analysis of posts regarding staying in work following stroke using the archives of an online forum for stroke survivors.Participants60 stroke survivors (29 male, 23 female, 8 not stated; mean age at stroke 44 years) who have returned to work, identified using terms ‘return to work’ and ‘back at work’.SettingPosts from UK stroke survivors and family members on Talkstroke, the forum of the Stroke Association, betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
109
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(115 citation statements)
references
References 20 publications
5
109
1
Order By: Relevance
“…It seemed as if cognitive impairment influenced the lost connection between body and world for most of the participants, which is in line with research that identified a changed sense of self and self-identity among young persons with stroke (10,(20)(21)(22)(23)(24). For the participants in this study, when the body did not work, this was, above all, most apparent in working life.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It seemed as if cognitive impairment influenced the lost connection between body and world for most of the participants, which is in line with research that identified a changed sense of self and self-identity among young persons with stroke (10,(20)(21)(22)(23)(24). For the participants in this study, when the body did not work, this was, above all, most apparent in working life.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have shown that persons with cognitive impairment after stroke experience difficulties in everyday life, as well as changes in sense of self and self-identity (18)(19)(20)(21) and self-body split (22). These impairments are commonly invisible (23,24), which has consequences for recovery, continuing to work and engaging in occupations over time.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding rates for all physicians were 58% and 64%, respectively (Ljungquist et al, 2015). For patients with a neurological diagnosis there is often a psychological impact to consider, and effects of such on work capacity is often more difficult to access which could be one reasons for why neurologists find it more difficult than other physicians to assess work capacity (Aghaei, Karbandi, Gorji, Golkhatmi, & Alizadeh, 2016;Balasooriya-Smeekens, Bateman, Mant, & De Simoni, 2016). The results regarding problems with assessing patients' work capacity are in line with results from other studies (Bränström et al, 2014;Kedzia et al, 2015;Ljungquist et al, 2015;Lofgren et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional methods of accessing parental views may exclude certain groups including those who are more geographically remote and those from culturally and ethnically diverse backgrounds 11 12. Logistics, time and discomfort in face-to-face and group interaction may deter some individuals.…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing focus on understanding the potential value of this method of data collection in qualitative research 13 14. Forums have successfully been used in healthcare research,15–20 providing a flexible and safe space, where open and honest discussions can be held over a period of months, in a conveniently non-synchronous way for potentially large numbers of users in different geographical areas 11 12 21. There is no burden on travel, and participation results in minimal disruption to daily life.…”
Section: Introductionmentioning
confidence: 99%